Pembangunan profesionalisme guru berdasarkan analisis keperluan latihan bagi guru sekolah kebangsaan di Terengganu / Alias Musa - Alias, Musa (2017)
The development of teachers‟ professional is needed in educational institutions to accelerate towards a continuous and systematic improvement. The process of transformation and innovation is intended by the Malaysian educational development blueprint 2013-2025 in order to realize the Malaysian educational system is excellent. This study was conducted to investigate the development of teachers‟ professionalism based on the training needs analysis for national schools in Terengganu which has focused on the teachers at national schools as respondent. Respondents involved in this study are 450 peoples from 331 Terengganu national schools. This study uses a questionnaire has been developed by myself to obtain the data. Stratified random sampling was used in selecting respondents. Methods of data analysis using descriptive and inference statistics by using the Statistical Package for the Social Science (SPSS) Version 22 and Partial Least Square of Structural Equation Model (Smart – PLS 3). The techniques of data analysis used in this study consist of descriptive statistics analysis, t-test, analysis of variance (ANOVA), and Structural Equation Model to determine the importance of training needs analysis and development model of teachers systematically. For the construct validity and questionnaire instrument is performed by using the analysis factor i.e. exploratory (EFA) and confirmatory factor analysis (CFA). This study shows that the level of implementation for training need analysis on the development of teacher‟s professionalism is high. Finding in this study indicates the training need analysis to the development of teacher‟s professionalism still not applied by sustainable and systematics at the School. In addition, this study was found that there are the differences the level of development of teacher‟s professionalism by demography factor in the Terengganu national schools. Furthermore, there is no effect of restriction variable as moderator to the development of teacher‟s professionalism. Finally, this study has been established the model of development of teacher‟s professionalism based on the training need analysis for the teacher‟s national schools in Terengganu. The researcher is expecting that the finding of this study can be becoming a guideline for all parties to study the training need analysis toward teacher‟s professionalism.